Pengaruh Metode Demonstrasi dan Motivasi Wali Kelas terhadap Prestasi Belajar Siswa MTs Wali Songo Ngabar Ponorogo - Yuni Vara Awalya; Jauhan Budiwan; Moh. Hazim Ahrori (BASICA, 2024)
Education is all the learning knowledge that occurs throughout life in all places and situations that have a positive influence on the growth of every individual. Islamic Religious Education exists as a form of effort and effort in the process of educating a person to be able to understand and animate in its entirety all the teachings contained in religion. However, the challenges faced in the learning process are often quite complex. Various external factors, such as family environment, socio-economic background, and educational policies, can also affect students' motivation and learning achievement. This research is a quantitativeresearch with a psychological approach. The population members in this study amounted to 238 students, while the sample was 75 students. In this study, the researcher used the probability sampling method while the method of taking simple random sampling was taken. To obtain the value of the data needed in this study, the researcher used questionnaire and documentation methods. The data analysis technique used is multiple linear analysis. The results showed that there was a positive and significant influence between the demonstration method and the learning achievement of MTsS Wali Songo Ngabar Ponorogo students with t-count values (79,389) > t-table (1,993). And the value of sig. 0.000< 0.05 can be stated that Ha is accepted and H0 is rejected. There is an influence between the motivation of homeroom teachers and the achievement of MTsS students of Wali Songo Ngabar Ponorogo. Evidence of the influence is taken from the results of analysis data processing with t-calculated values (89,561)> t-table (1.993). And the value of sig. 0.000< 0.05 which means that Ha is accepted and H0 is rejected. There is a positive and significant influence between the demonstration method and the motivation of the homeroom teacher on the learning achievement of MTsS Wali Songo Ngabar Ponorogo students. This is evidenced by the value of f-calculation > f- table (51,610 > 2,730). And the value of sig. 0.000< 0.05, then Ha is accepted and H0 is rejected. Thus, it can be concluded that there is a significant correlation between the demonstration method and the motivation of homeroom teachers on student learning achievement.